Reading History in the Roman Empire - Baumann, Mario; Liotsakēs, Basilēs (2022)
Spanning the time from the 1st century BCE to the 400s CE, this volume highlights the multifaceted interactions between Greco-Roman historiographical texts and their readers. Its contributions focus on the testimonies offered by ancient readers themselves and they engage in close readings of the historiographical works to explore how these texts involve their audiences and stimulate a fascinating range of intellectual and affective reactions.